The Older They Are, the Less Successful They Become? Findings from the Georgia Centenarian Study - Jinmyoung Cho; Peter Martin; Leonard W. Poon (Journal of Aging Research)
This study examined whether oldest-old adults are successful agers. Three hundred and six octogenarians and centenarians of Phase III of the Georgia Centenarian Study participated in this study. A first model examined Rowe and Kahn’s successful aging model (Rowe and Khan (1997 and 1998)) including the probability of disease, physical or cognitive capacity, and engagement with life. All three components were applied to assess how many oldest-old adults satisfied all three criteria. The result showed about 15% of octogenarians (15.1%), and none of centenarians satisfied all three components of successful aging. Consequently, a second alternative model focused on psychosocial aspects including three different components: subjective health, perceived economic status, and happiness. Different from Rowe and Kahn’s successful aging model, a total of 62.3% of octogenarians and 47.5% of centenarians satisfied all three components of the alternative model of successful aging. The results suggest that additional criteria of successful aging should be considered thereby expanding the concepts and multidimensional aspects of successful aging among oldest-old adults.